2020
DOI: 10.1038/s41388-020-1305-5
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 activates p53 by enhancing PCAF-mediated MDM2 degradation to arrest the cell cycle

Abstract: Sirtuin 7 (SIRT7), an NAD +-dependent deacetylase, plays vital roles in energy sensing, but the underlying mechanisms of action remain less clear. Here, we report that SIRT7 is required for p53-dependent cell-cycle arrest during glucose deprivation. We show that SIRT7 directly interacts with p300/CBP-associated factor (PCAF) and the affinity for this interaction increases during glucose deprivation. Upon binding, SIRT7 deacetylates PCAF at lysine 720 (K720), which augments PCAF binding to murine double minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…However, other reports indicated that SIRT7 lacked p53 deacetylation activity [14,27]. Recently, overexpression of SIRT7 led to increased p53 stability, but SIRT7 does not deacetylate p53 in vitro or in HT1080 or NHF cells [36]. Our findings on SIRT7 modulating p53 function through deacetylating STRAP added new insight into SIRT7-p53 regulation and reconciled the controversial studies.…”
Section: Discussionsupporting
confidence: 69%
“…However, other reports indicated that SIRT7 lacked p53 deacetylation activity [14,27]. Recently, overexpression of SIRT7 led to increased p53 stability, but SIRT7 does not deacetylate p53 in vitro or in HT1080 or NHF cells [36]. Our findings on SIRT7 modulating p53 function through deacetylating STRAP added new insight into SIRT7-p53 regulation and reconciled the controversial studies.…”
Section: Discussionsupporting
confidence: 69%
“…SIRT7 physically binds and deacetylates P300/CBP-associated factor (PCAF) at K720, and this interaction is enhanced under conditions of glucose deprivation. As a result, PCAF binding to MDM2 is promoted, resulting in a triggering of MDM2 degradation via the ubiquitin-dependent proteasome pathway (Lu Y. F. et al, 2020). Finally, in p21-KO lymphomas, p27 Kip1 (CDKN1B) functions in a p21-independent manner to induce cell cycle arrest after SAHA treatment (Newbold et al, 2014).…”
Section: Cell Cyclementioning
confidence: 99%
“…A novel SIRT7 inhibitor has been identified to inhibit tumor growth by blockade of the direct interaction of SIRT7 and p53 (Vakhrusheva et al, 2008;Kim J. H. et al, 2019). However, there are also several reports demonstrating an indirect interaction between SIRT7 and p53 (Barber et al, 2012;Lu Y. F. et al, 2020;Yu et al, 2020). Thus, it is urgent to develop specific SIRT inhibitors for cancer therapy according to reasonable mechanisms.…”
Section: Limitations Of Hdacimentioning
confidence: 99%
“…In a recent study, it was shown that under glucose starvation SIRT7 elevates p53 protein levels by destabilizing MDM2. 6 Mechanistically, SIRT7 deacetylates the acetyltransferase PCAF (p300/CBP-associated factor) thereby promoting binding of PCAF to MDM2, which will eventually destabilize MDM2 (Figure 1b). 6 Interestingly, we found that SIRT7 has no impact on MDM2 stability following UVirradiation, indicating that SIRT7 inhibits MDM2 either by deacetylating NPM or PCAF.…”
Section: Author´s Viewmentioning
confidence: 99%